MINING SECURITY PIPE© (TSM)© WITH UNDERGROUND GPS GLOBAL© (RSPG)© ESCAPE SECURITY DEVICE IN UNDERGROUND MINING - Rafael Barrionuevo GIMÉNEZ (Management Systems in Production Engineering, 2016)
TSM is escape pipe in case of collapse of terrain. The TSM is a passive security tool placed underground to connect the work area with secure area (mining gallery mainly). TSM is light and hand able pipe made with aramid (Kevlar), carbon fibre, or other kind of new material. The TSM will be placed as a pipe line network with many in/out entrances/exits to rich and connect problem work areas with another parts in a safe mode. Different levels of instrumentation could be added inside such as micro-led escape way suggested, temperature, humidity, level of oxygen, etc.). The open hardware and software like Arduino will be the heart of control and automation system.